Resiliency of prefabricated daycares and schools: Finnish perspective to relocatable education facilities - Edelman, Harry; Vihola, Jaakko; Laak, Mikko; Annila, Petri (International Journal of Strategic Property Management, 2016)
The industrialised production of prefabricated daycare and school properties offer flexible alternatives for communities for provision of communal services. The paper investigates architectural qualities and financial solutions for rentable and relocatable education facilities in finland. in particular, the focus is on the communal interests in solving the property management with a portfolio of rentable facilities for different time spans ranging from very short term to periods up to over twenty years. The short term rental terms offer solutions for disaster mitigation such as flooding but also spaces during refurbishment of existing buildings, e.g. due to moisture and mould damage. A core issue is a potential sustainable and flexible co-existence of both permanent and flexible modules that can adapt, for example to demographic changes, improving the efficiency of communal property management. Thus the prefabricated solutions have a potential, if the architectural quality is high enough, to provide alternatives for the real estate strategies of cities also in longer term provision of daycare and school facilities.